Discrete Global Grid Systems with quadrangular cells as reference frameworks for the current generation of Earth observation data cubes. (April 2023) - Béjar, Rubén; Lacasta, Javier; Lopez-Pellicer, Francisco J.; Nogueras-Iso, Javier
Abstract: Discrete Global Grid Systems are spatial reference frameworks that associate information to multi-resolution grids of uniquely identified cells; they are proposed as mechanisms to facilitate the efficient integration of heterogeneous spatial data. They could provide an excellent reference system for Earth observation data cubes, technological infrastructures that provide analysis-ready access to Earth Observation big data, as long as they can be made compatible with them. In this paper, we demonstrate that this is currently feasible without requiring new technological developments. We show how a Discrete Global Grid System with quadrangular cells, rHEALPix, and an existing data cube platform, Open Data Cube, can be integrated without loosing the advantages of having all the data in a Discrete Global Grid System, while keeping a straightforward access to all of the analysis tools provided by an Earth Observation Data Cube. Highlights: Processing datasets in Discrete Global Grid Systems may require new tools. However, current Earth observation data cubes can process some DGGS datasets. This is possible with quadrangular cells, and the right data pre-processing steps. It does not require any technological developments in the data cubes. The processed datasets keep the original DGGS structure (resolution, alignment etc.).